Photoresponsive polymer–quantum dot nanocomposites for targeted therapy - Borzouyan Dastjerdi, Mahsa; Khoda dadi, Reza; Hosseinzadeh, Jalaladdin (Journal of Composites and Compounds, 2025)
This perspective explores the promising role of photoresponsive polymer–quantum dot nanocomposites in targeted therapy. These materials are notable for their ability to allow controlled drug release while simultaneously providing real-time imaging capabilities. The focus is on developing biocompatible and multifunctional platforms that address existing issues such as toxicity and stability. Such innovations could result in more personalized, image-guided cancer treatments that offer greater precision and safety.